Human organ donation and spirituality: a multicentre observational study aimed at healthcare professionals who work in the Italian context - Bolgeo, T.; Ruta, F.; Damico, V.; Pancani, L.; Bertolotti, M.; Gambarini, L.; Cassinari, A.; Gatti, D.; Maconi, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Aim. This study aimed to assess if spirituality could be a predictor of organ donation, using a descriptive/ knowledge survey aimed at healthcare professionals working in Italy. Methods. This multicentre, descriptive observational study was conducted in three Italian regions (Lombardy, Piedmont and Apulia). Two scales were used for the data collection: the Organ Donation Attitude Scale (ODAS) to explore the healthcare staff’s attitudes towards organ donation and the Spiritual Health LifeOrientation Measure (SHALOM) to explore their perception of the concept of spirituality. Results. The sample included 688 healthcare professionals (460 females, 66.9%). The analysis of their attitudes, assessed as their predisposition to organ donation, evidenced the women’s higher degree of agreement regarding the safety and effectiveness of the practice (40.7% versus 31.1%, p = 0.001). The sample showed a high positive attitude towards organ donation (M = 4.25, SD = 0.50), whereas the level of spirituality was slightly lower than the midpoint of the Likert scale (M = 2.76, SD = 1.31). Spirituality positively predicted the positive attitude towards organ donation among Lombard professionals with shorter (–1 SD) careers (b = 0.078, p = 0.044) and among both Piedmontese (b = 0.250, p < 0.001) and Apulian (b = 0.458, p < 0.001) professionals with longer (+1 SD) careers. Discussion. Regarding organ donation, the surveyed healthcare professionals showed higher scores in the positive attitude section and lower scores in the negative attitude section, regardless of the geographical context of reference.